Evaluation of an intraventricular balloon pump for short‐term support of patients with heart failure. Issue 9 (11th April 2019) - Boone, Alice C.; Gregory, Shaun D.; Wu, Eric L.; Stephens, Andrew; Liao, Sam; Pauls, Jo P.; Salamonsen, Robert; Fraser, John; Tansley, Geoff D.
Abstract: The high cost of ventricular assist devices results in poor cost‐effectiveness when used as a short‐term bridging solution, thus a low‐cost alternative is desirable. The present study aimed to develop an intraventricular balloon pump (IVBP) for short‐term circulatory support, and to evaluate the effect of balloon actuation timing on the degree of cardiac support provided to a simulated in vitro severe heart failure (SHF) patient. A silicone IVBP was designed to avoid contact with internal left ventricular (LV) features (ie, papillary muscles, chordae, aortic, and mitral valves) based on LV computed tomography data of 10 SHF patients with dilated cardiomyopathy. The hemodynamic effects of varying balloon inflation and deflation timing parameters (inflation duty [D] and end‐inflation point [σ]) were evaluated in a purpose‐built systemic mock circulatory loop. Three IVBP actuation timing categories were defined: co‐, transitional, and counterpulsation. Compared to the SHF baseline, co‐pulsation increased aortic flow from 3.5 to 5.2 L/min, mean arterial pressure from 72.1 to 94.8 mmHg and ejection fraction from 14.4% to 21.5%, while mean left atrial pressure decreased from 14.6 to 10 mmHg. Transitional and counterpulsation resulted in a double ventricular pulse and extended the duration of increased ventricular pressure, potentially impeding diastolic filling and coronary perfusion. This in vitro study showed the IVBP could restore the hemodynamic balance of a simulated SHF patient with dilated cardiomyopathy to healthy levels.